2007
DOI: 10.1021/es070713i
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Octyl- and Nonylphenol Ethoxylates and Some Carboxylated Derivatives in Three American Wastewater Treatment Plants

Abstract: The fate of a comprehensive group of nonylphenol and octylphenol ethoxylates (APEOs) and several of their carboxylated derivatives was studied in three American wastewatertreatment plants (WWTPs), two of which included advanced treatment. Influent and effluent concentrations of the alkylphenolic compounds (APEs) in the three plants were very similar, but effluent concentrations showed a seasonal dependency: both carboxylate and ethoxylate concentrations in the effluents were higher in winter than in summer. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 21 publications
9
47
2
Order By: Relevance
“…It is clear that the total concentrations of nonylphenolic compounds (NP-c) in the dry weather is related to industrial and domestic wastewater content in the WWTPs influents, i. e., 0.115 to 0.183 μmol/L of NP-c in the WWTPs receiving both industrial and domestic wastewaters, and 0.347 μmol/L of NP-c in the WWTP receiving only domestic wastewater. The concentrations of nonylphenolic compounds detected in this study fell into the range reported in other literatures (Ma et al, 2002;Planas et al, 2002;Hou and Sun, 2006;Stasinakis et al, 2008), but were at low level compared to those observed in the European countries, such as Switzerland (2.42-4.05 μmol/L) (Ahel et al, 1994) and United States (425-894 μg/L for NP0-16EO) (Loyo-Rosales et al, 2007), indicating that the contamination in Beijing seemed less heavy than abroad, probably due to less consumption of NPnEOs surfactants in Beijing.…”
Section: Npneos and Their Metabolites In The Influents And Effluents supporting
confidence: 68%
See 4 more Smart Citations
“…It is clear that the total concentrations of nonylphenolic compounds (NP-c) in the dry weather is related to industrial and domestic wastewater content in the WWTPs influents, i. e., 0.115 to 0.183 μmol/L of NP-c in the WWTPs receiving both industrial and domestic wastewaters, and 0.347 μmol/L of NP-c in the WWTP receiving only domestic wastewater. The concentrations of nonylphenolic compounds detected in this study fell into the range reported in other literatures (Ma et al, 2002;Planas et al, 2002;Hou and Sun, 2006;Stasinakis et al, 2008), but were at low level compared to those observed in the European countries, such as Switzerland (2.42-4.05 μmol/L) (Ahel et al, 1994) and United States (425-894 μg/L for NP0-16EO) (Loyo-Rosales et al, 2007), indicating that the contamination in Beijing seemed less heavy than abroad, probably due to less consumption of NPnEOs surfactants in Beijing.…”
Section: Npneos and Their Metabolites In The Influents And Effluents supporting
confidence: 68%
“…Regarding the effluents of WWTPs, NPECs were as expected the most abundant group (Fig. 1b), indicating NPECs were the main metabolites of NPnEOs during biological degradation processes (Ahel et al, 1994;Loyo-Rosales et al, 2007).…”
Section: Npneos and Their Metabolites In The Influents And Effluents supporting
confidence: 68%
See 3 more Smart Citations